Estimating thresholds of nitrogen, phosphorus and potassium fertilizer rates for rice cropping systems in China - Liu, Yingxia; Ding, Wencheng; He, Ping; Xu, Xinpeng; Zhou, Wei (Frontiers in plant science, 2024)
Determining the fertilization rate plays a pivotal role in agronomic practices as they directly impact yield targets, soil fertility, and environmental risks. In this study, we proposed a method that utilizes allowed ranges of partial nutrient balance and yield to estimate the threshold of nitrogen (N), phosphorus (P), and potassium (K) fertilizer applied to rice ( Oryza sativa L.) fields in China. Based on a dataset of 6792 observations from rice fields, we determined the minimum and maximum rates of N, P and K suggested for single (mono-season rice), middle (summer-season rice rotated with winter-season upland crop), early and late (double-season rice cropping system) rice, ranging between 114−146 and 220−292 kg N ha −1 per season, 56−74 and 112−149 kg P 2 O 5 ha −1 per season, and 170−230 and 329−347 kg K 2 O ha −1 per season, respectively. These values serve as the lower and upper fertilization thresholds, guiding yield goals and environmental protection. Furthermore, if rice straw is returned to fields, the demand for K fertilizer can theoretically decrease by 183 kg K 2 O ha −1 , with corresponding decreases of 50 kg N ha −1 and 26 kg P 2 O 5 ha −1 , respectively. A recommended fertilization approach, excluding returned straw nutrients from the upper fertilization thresholds, suggested average application rates of 194 kg N ha −1 , 105 kg P 2 O 5 ha −1 , and 157 kg K 2 O ha −1 , which align well with the nutrient requirements of rice. Additionally, substituting organic N for chemical N is an effective approach to conserve chemical fertilizer N, potentially reducing chemical N usage by 20%−40%. Utilizing slow-release N is also a favorable option to enhance N use efficiency and optimize N balance. This study offers valuable insights into the development of fertilization restriction indicators, aiming to achieve a delicate balance between environmental impact and agricultural productivity through the adoption of balanced fertilization rates and utilization of organic residues.